A Stopgap Solution for EON Resource Assignment Postponing the Need for Disruptive Technologies - Xu, Yuxin; Xing, Hang; Chen, Bin (2023 Asia Communications and Photonics Conference/2023 International Photonics and Optoelectronics Meetings (ACP/POEM), 2023)
In order to enhance the network throughput for modern fiber optic networks, disruptive capacity-expanding technologies are emerging, such as spatial division multiplexing or adding L-band transmission, at the cost of enormous expenditure in labor, capital, and time. A stopgap solution is proposed in this paper to meet increasing communication needs in the short term before costly capacity-expanding techniques are needed. The proposed impairment-aware algorithm uses hybrid modulation and signal regeneration to achieve a 148 Tbps total network throughput in C-band, a 42% enhancement over the benchmark, when tested in the NSF-24 network with realistic population-based traffic. The proposed algorithm can be used as a stopgap relying mostly on existing infrastructure to temporarily ease the increasing throughput pressure.